The influence of N2 plasma treatment on the optical bandgap and photoluminescence of orderly nanoporous TiO2 film. (25th September 2019) - Wang, Manli; Chen, Zixuan; Cong, Zhezhe; Liu, Lihu; Sun, Huiyuan
Abstract: Amorphous-like structural orderly nanoporous titanium dioxide thin films were prepared at room temperature by dc reactive magnetron sputtering. It was found that the optical properties of the films depended on the pore diameters and influenced by the post plasma treatment in nitrogen atmosphere, but it seemed that the thickness of the film had no more influence on them. The results showed that the nitrogen plasma treatment was responsible for lowering of the energy bandgap values due to the increase in oxygen vacancy defects of the films, which could be proved by the photoluminescence results. The mechanism for changing of optical bandgaps is discussed in detail in this paper. Absorbance of the amorphous nanoporous TiO2 thin films was calculated using UV-visible NIR spectrophotometer. The morphology of the deposited film was studied by scanning electron microscopy (SEM) and atom-force microscopy (AFM), respectively. The results can be interesting towards the development of nanoporous TiO2 thin films with defined structure and optical properties.